PENGARUH ABSENSI, KEDISIPLINAN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DAN DAMPAKNYA PADA KINERJA ORGANISASI BIRO UMUM SEKRETARIAT DAERAH ACEH - Gamal Abdul Nasir; Mukhlis Yunus; Teuku Roli Ilhamsyah Putra (Jurnal Magister Manajemen, 2018)
The purpose of this study is to determine the effect of absenteeism, discipline and leadership style on employee performance and its impact on the performance of the organization of the Regional Bureau of the Aceh Regional Secretariat. The population of this study is all employees of the General Bureau of the Aceh Regional Secretariat which currently number 285 people, the sampling technique used in this study is the method of "Simple Random Sampling" to 50 percent of the total population so that the number of samples obtained as many as 143 respondents. There is the influence of discipline, leadership style and absenteeism on the performance of the employees of the Aceh Secretariat General Bureau. There is an influence of employee discipline, leadership style, absenteeism, and performance of employees on the performance of the General Bureau of the Aceh Secretariat. There is the influence of discipline, leadership style and absenteeism through employee performance on the performance of the General Bureau of the Aceh Secretariat